2023
DOI: 10.1002/macp.202200460
|View full text |Cite
|
Sign up to set email alerts
|

High Ion Conducting Dobule Network Crosslinked Gel Polymer Electrolytes for High‐Performance Supercapacitors

Abstract: As the demand for electrical energy storage devices increases, various electrolytes are being studied. In particular, gel polymer electrolytes (GPEs) with excellent physical properties can improve safety and cycle life, so attempts are underway to replace organic liquid electrolytes facing fire or explosion issues. However, the intrinsic poor electrochemical properties of GPEs limit their commercialization in all-solid-state energy storage devices. In an attempt to solve this problem, epoxy/poly(ethylene glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The characteristic peak at ∼1728 cm −1 belonged to the C]O originating from PEGDMA, which provided good affinity between the polymer skeleton and the electrolyte. 27 It is noteworthy that the characteristic peaks of AN (2260 cm −1 for -CN group), 29 PC (1780 cm −1 for aliphatic ketone group), 30 and IL (1347 and 1175 cm −1 for the TFSI anion; 3100-3160 cm −1 for the imidazolium cation) 31 appeared in the fabricated P2A or P2P as well, suggesting that considerable amounts of the organic solvents and IL were still retained in the | Sustainable Energy Fuels, 2024, 8, 358-368…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic peak at ∼1728 cm −1 belonged to the C]O originating from PEGDMA, which provided good affinity between the polymer skeleton and the electrolyte. 27 It is noteworthy that the characteristic peaks of AN (2260 cm −1 for -CN group), 29 PC (1780 cm −1 for aliphatic ketone group), 30 and IL (1347 and 1175 cm −1 for the TFSI anion; 3100-3160 cm −1 for the imidazolium cation) 31 appeared in the fabricated P2A or P2P as well, suggesting that considerable amounts of the organic solvents and IL were still retained in the | Sustainable Energy Fuels, 2024, 8, 358-368…”
Section: Resultsmentioning
confidence: 99%
“…DSC analysis ( Figure 3 a) confirmed that both composite membranes are completely polymerized, by the absence of residual heat or an exothermal peak, in agreement with previous observations by ATR-FTIR. In addition, negative glass transition temperatures (T g ) of −58 °C and −59 °C were found for CGPE-GFA and CGPE-GFW, respectively, which, combined with the presence of amorphous phases, are essential for delivering a high ionic conductivity by segmental motion of the ethylene oxide chains above T g [ 27 ]. In this case, it is expected that at room temperature both membranes could provide appropriate Li + ion hopping, and a high ionic conductivity.…”
Section: Resultsmentioning
confidence: 99%